A review of the synthetic transport fuels as a solution for carbon neutrality - Rodica Niculescu; Adrian Clenci; Alireza Shirneshan; Mihaela Năstase (Next Energy)
In the current context in which greenhouse gas (GHG) emissions, global warming, and poor energy security are paramount, finding new sources of sustainable, renewable energy has become a top priority. The transportation sector is accountable for a significant percentage of GHG emissions. Therefore, the decarbonization of transport is a priority.Today, the significance of energy in economics and politics is undeniable. As a result, the production of alternative fuels is not merely an option but a necessity. The objective of this review is to outline the findings of recent studies regarding potential methods for attaining carbon neutrality in the transportation sector through the utilization of synthetic fuels. This review presents the potential of combining fossil fuel sources with carbon capture and storage technologies to reduce the greenhouse effect. The main CO2 capture technologies, such as post-combustion, pre-combustion, oxyfuel combustion, and direct air capture (DAC), were also explained. The review also discusses ways of using the captured CO2 to obtain value-added products, including fuels, through various approaches like electrochemical, thermal, biochemical, chemo-enzymatic, and photocatalytic methods. However, the review highlights that catalysts are an area where research must continue intensively in the future. Furthermore, the review evaluates the combustion characteristics, performance, and emissions of engines fueled with synthetic fuels, such as Fischer-Tropsch diesel and oxymethylene dimethyl ethers (OMEx), in comparison to fossil diesel fuel. The challenges related to the production cost estimation of these synthetic fuels are also presented, as they involve economic uncertainties and a large number of parameters. The review also discusses the life cycle analysis of synthetic fuels produced from CO2, considering the sources and processes for obtaining hydrogen and CO2, their transport and storage, the production processes of synthetic fuels, and their transport and use. In addition, the review addresses the barriers and opportunities for the commercial deployment of synthetic transport fuels and the policy implications, as well as presenting several companies around the world that have begun to develop ambitious synthetic fuel manufacturing projects as an alternative to fossil fuels. Finally, the review presents the challenges and perspectives of synthetic transport fuels as a solution for carbon neutrality.